Music Appreciation and Training for Cochlear Implant Recipients: A Review - Looi, Valerie; Gfeller, Kate; Driscoll, Virginia D. (Seminars in Hearing, 2012)
In recent years, there has been increasing interest in music perception of cochlear implant (CI) recipients and a growing body of research conducted in this area. The majority of these studies have examined perceptual accuracy for pitch, rhythm, and timbre. Another important, but less commonly studied aspect of music listening is appreciation, or appraisal. Despite the ongoing research into potential technological improvements that may improve music perception for recipients, both perceptual accuracy and appreciation generally remain poor for most recipients. Although perceptual accuracy for music is important, appreciation and enjoyment also warrant research as they contribute to clinical outcomes and perceived benefits. Music training offers excellent potential for improving music perception and appreciation for recipients. Therefore, the primary topics of this review are music appreciation and training. However, a brief overview of the psychoacoustic, technical, and physiological factors associated with a recipient's perception of music are provided, as these are important factors in understanding the listening experience for CI recipients. The purpose of this review is to summarize key articles that have investigated these issues, to demonstrate that (1) music enjoyment and appraisal is an important and valid consideration in evaluating music outcomes for recipients, and (2) that music training can improve music listening for many recipients, and is something that can be offered to persons using current technology.
Keywords: cochlear implants; music; quality of life; rehabilitation; training; sound quality